(untitled) - Sawicki, Ed (Australia, 2006)
Linux is the fastest growing operating system. As the number of companies implementing Linux increases, so too does the rapidly-developing need for skilled users, developers and administrators. Advanced Guide to Linux Networking and Security was especially designed for individuals who want to move beyond just the basics of Linux installation and administration into a broader study of the many security issues surrounding this operating system. With its comprehensive Linux security coverage, this text can fit into any Linux Security course and is intended to follow the Complete Guide to Linux System Administration by Nick Wells.
Keywords: Linux,Hệ điều hành Linux